2019
DOI: 10.1159/000500885
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Oncological Treatment and Tumor Mass in Non-Small Cell Lung Cancer: Case-Control Analysis of Overall Survival in Routine Clinical Practice

Abstract: <b><i>Background:</i></b> Immuno-oncological (IO) therapies such as PD-1 and PD-L1 antibodies have been introduced in the treatment of advanced non-small cell lung cancer (NSCLC) since 2015 based on randomized trials showing unprecedented advantages in overall survival (OS) with hazard ratios (HRs) between 0.5 and 0.7. The impact of these treatments on OS in routine clinical practice and the role of tumor mass have not been studied. <b><i>Methods:</i></b> 557 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…7,19 A potential benefit from adding chemotherapy to ICI is that in mNSCLC, the benefit with ICI monotherapy tended to be greater in patients with lower tumor burden, although these data are limited and retrospective. 52 By contrast, a post hoc aanlysis from KEYNOTE-189 reported that the survival outcome with combination occurred regardless of the baseline tumor burden (defined as ≤ 3 or > 3 median number of organ systems involved). 53 This may suggest that patients with more indolent disease or less symptom burden may be optimal for single-agent immunotherapy (Fig 6).…”
Section: Clinical Decisionsmentioning
confidence: 98%
“…7,19 A potential benefit from adding chemotherapy to ICI is that in mNSCLC, the benefit with ICI monotherapy tended to be greater in patients with lower tumor burden, although these data are limited and retrospective. 52 By contrast, a post hoc aanlysis from KEYNOTE-189 reported that the survival outcome with combination occurred regardless of the baseline tumor burden (defined as ≤ 3 or > 3 median number of organ systems involved). 53 This may suggest that patients with more indolent disease or less symptom burden may be optimal for single-agent immunotherapy (Fig 6).…”
Section: Clinical Decisionsmentioning
confidence: 98%
“…ICIs have significant benefits in OS compared with traditional chemotherapy in the casecontrol analysis [13]. There was no considerable difference in OS and DFS between PD1 and PDL1 inhibitors, but odd ratios of pembrolizumab (PDL1 expression ≥ 50% ) and nivolumab (PDL1 expression ≥ 1%) were higher than that of atezolizumab [12].…”
Section: Overall Survival and Progression-free Survival Of Immune Chementioning
confidence: 88%
“…Although tumor load was available as a variable in this study, it was excluded due to missing information. Faehling, Schwenk, Kopp, Fallscheer, Kramberg, and Eckert [23] has shown that tumor load is an essential factor for overall survival, and patients with lower tumor load have a better outcome than patients with larger tumor load. PLNS, on the other hand, was unavailable in this study which makes the structural comparison somewhat unfair.…”
Section: Discussionmentioning
confidence: 99%